Предмет: Алгебра,
автор: Espe
Упростите выражение а (а+1)-(а-3)² и найдите его значение при а= -1. В ответ запишите полученное число.
Ответы
Автор ответа:
0
a(a+1)-(a-3)²=a²+a-((a-3)(a-3))=a²+a-(a²-3a-3a+9)=
=a²+a-a²+6a-9=7a-9
при а=-1
7*(-1)-9=-7-9=-16
=a²+a-a²+6a-9=7a-9
при а=-1
7*(-1)-9=-7-9=-16
Похожие вопросы
Предмет: Английский язык,
автор: aigerimalybaeva3
Предмет: Алгебра,
автор: Аноним
Предмет: Информатика,
автор: AnastasiaTer23
Предмет: Литература,
автор: Аноним
Предмет: Химия,
автор: Evgenua